Science and Technology of Novel Integrated Biocompatible Superparamagnetic Oxide Nanoparticles Injectable in the Human Eye and External Ultrananocrystalline Diamond (UNCD™)-Coated Magnet for a New Retina Reattachment Procedure - Saravia, Mario Joaquin; Zysler, Roberto Daniel; Lima, Enio Junior; Gurman, Pablo; Auciello, Orlando (Cambridge University Press, 2022)
Fil: Saravia, Mario Joaquin. Universidad Austral; Argentina